The collective recruitment management in the origin of temporary colombians in the province of LLeida - M. Gordo Márquez; R. Allepuz Capdevila; Juan Antonio Márquez Domínguez; T. Torres Solé (Boletín de la Asociación de Geógrafos Españoles, 2015)
Texto resumen.